Development and Validation of an In-House Library for Filamentous Fungi Identification by MALDI-TOF MS in a Clinical Laboratory in Medellin (Colombia) (2020)
ABSTRACT: Identification of filamentous fungi by conventional phenotypic methods are time-consuming, and a correct identification at the species level is prone to errors. Therefore, a more accurate and faster time-to-results, and cost-effective technique, is required, such as the Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS). In this study, we describe the development of an in-house spectra library for the identification of filamentous fungi frequently isolated from patients with infections. An in-house spectra library was constructed using 14 reference strains grown in solid medium. Clinical isolates were identified either by the in-house spectra library or the Biotyper commercial library from Bruker Daltonics. Fungal identification was carried following the Biotyper’s established scores: ≤1.699: not reliably identified (NRI); 1.700–1.999: genus-level; ≥2.000: species-level. Clinical isolates were identified, with the in-house library, at species- and genus-level at 88.70% (55) and 3.22% (2), respectively. While 4.80% (3) was NRI and 3.22% (2) was discrepant concerning sequencing. On the contrary, identification up to species and genus-level with the commercial library was 44.44% (16) and 22.22% (8), respectively. NRI and the discrepancy was 30.55% (11) and 2.77% (1), respectively. For the reaming 26 isolates, 16 from Neoscytalidium dimidiatum and 10 from Sporothrix spp., respectively, the absence of spectrum and the specific spectra within the Sporothrix complex in the commercial library resulted in the inability to obtain an identification. In conclusion, the current results advocate the importance that each clinical microbiological laboratory needs to develop an ad hoc library associated with the MALDI-TOF MS fungal identification to overcome the limitations of the available commercial libraries.